Association In Number Of Red Blood Cell Units Transfused And The Outcome Of Discharge At Different Haemoglobin Levels In Acute Non-Variceal Upper Gastroinstestinal Bleeding Patients At Hospital Putrajaya - Yusop, Mohd Faeiz (2019)
Background: Non-Variceal Upper Gastrointestinal Bleeding (NVUGIB) is very common and with considerable 5-10% mortality. RBC transfusion is one of the treatments for NVUGIB patients but it is associated with various morbidity and mortality. This study was to determine the associations between number of RBC units transfused with presenting symptoms, aetiologies and Glasgow-Blatchford Score (GBS). This study also compared the outcomes of discharge at different level of Hb among NVUGIB patients at Hospital Putrajaya. Methods: Retrospective cohort study was performed with data from 180 patients with NVUGIB and were transfused with RBC over a period of five years. Data were retrieved from the computerised patient information system of Hospital Putrajaya. Study subjects selected were filled in the proforma. All demographic and clinical data including presenting symptoms such as melaena, haematemesis, haematochezia, and anaemia were recorded. Besides presenting symptoms, other variables studied include aetiologies of NVUGIB, GBS, and number of RBC units transfused. The clinical outcomes of patients with two different level of discharge Hb were compared. Results: Out of 180 patients, 92 (51.1%) had discharge Hb < 10 g/dl while 88 (48.9%) of them had discharge Hb ≥ 10 g/dl. Using multiple linear regression, haematochaezia (p=0.022) and higher GBS (p<0.001) were factors which were independently associated with higher number of RBC units transfused. Using Mann Whitney-U test, patients with discharge Hb ≥ 10 g/dl were shown to be significant contributor to higher number of RBC units transfused (p=0.005) and longer length of stay (LOS) (p=0.029). Conclusion: Haematochaezia and GBS were two important determinants for the probability of higher need in RBC unit transfusion for NVUGIB patients. Patients with discharge Hb ≥ 10 g/dl will result in higher number of RBC units transfusion and longer LOS.